APPLICATION OF DISCOVERY LEARNING MODELS WITH HEURISTIC APPROACH (CRULIC AND RUDNIC) TO IMPROVE THE STUDENTS MATHEMATICAL PROBLEM-SOLVING SKILLS - Reni Mustika Nugraheni; Uus Kusdinar (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The approach to learning mathematics used in class X of SMA Negeri 1 Prambanan 2018/2019 academic year is still not encouraging students to take an active part in learning activities, allegedly to be one of the causes of the lack of students' mathematical problem-solving skills. This study aims to improve mathematical problem-solving skills by applying the Guided Discovery Model with the Krulik and Rudnick Heuristic Approach to the inequalities of two variables. This type of research is Clas Action research Research (CAR). This study's subject was students of class X Science Mathematics (MIPA) 4 State Senior High School (SMA Negeri) Prambanan 1 the Academic year 2018/2019 with 32 students. Simultaneously, the object in this study is the whole process of applying the Guided Discovery Model with the Krurik and Rudnik Heuristic Approach. Data collection techniques are carried out through student observation techniques, interviews, and documentation. Instrument data collection in the form of observation sheets, the completion of practice questions of students' mathematical problem-solving skills, and the results of interviews. Test instruments are used in the form of validation. Technical data analysis uses descriptive methods. This study's results indicate that applying the Guided Discovery Model with the Heuristic Approach Type Krulik and Rudnik can improve students' mathematical problem-solving skills. The improvement of students 'mathematical problem-solving skills can be seen from the average results of completing the practice questions of students' mathematical problem-solving skills from the Low category with 29.34% in the first cycle to Very High 80.816% in cycle II.